Avaliação de um curso sobre internet para terceira idade - Dotta, Edivani Aparecida Vicente [UNESP]; Pova, Allan pedro Moreira [UNESP]; Brunelli, Julia Vila Verde [UNESP]; Maschetto, Ana Luiza Rossete [UNESP]; Costa, Marina Aidar Monteiro da [UNESP]; Campos, Juliana Alvares Duarte Bonini [UNESP]; Garcia, Patrícia Petromilli Nordi Sasso [UNESP] (My University, 2012)
The aim of this study was to evaluate the learning of Senior Citizens after a face-to-face course with the goal of teaching them how to use the internet. The study population was composed of people (n=18), of both genders, aged 50 years or over, from the open university for Senior Citizens UNATI (“Universidade Aberta da Terceira Idade” in Portuguese) at Araraquara. Two hour classes weekly were taught in the computer laboratory - LDI in Portuguese located in the School of Dentistry in Araraquara. The course program content covered the use of e-mail and researches in sites. In order to evaluate the learning acquired, a self-evaluation questionnaire was applied in twice (before and after the course), which enabled the development of students concerning their knowledge and skill in the topics approached in classes. Descriptive statistical analysis was performed. The average performance of participants was calculated per point and interval of confidence of 95% (IC95%) in the beginning and in the end of the course. Comparison between the averages was performed by using the paired Student’s-t test. The level of significance adopted was 5%. It was observed that the students’ learning about computer use improved significantly after the course (Student’s-t test: -5.360, p<0.001, p2=0.628, =0,999), however, 72.2% of them reported that they did not know how to attach a file to a message to be sent by e-mail, as well as having no or little skill to perform this activity. It was concluded that the evaluated course improved the participants knowledge and skills in computer use.

O objetivo desse trabalho foi avaliar a evolução do aprendizado de indivíduos pertencentes à terceira idade após a aplicação de um curso presencial voltado para o ensino da utilização da internet. A população de estudo foi composta por indivíduos (n=18), de ambos os sexos, com idade igual ou superior a 50 anos, oriundos da UNATI (Universidade Aberta da Terceira Idade) de Araraquara. As aulas foram ministradas no Laboratório Didático de Informática (LDI) alocado na Faculdade de Odontologia de Araraquara, com periodicidade semanal e duração de duas horas cada. O conteúdo programático do curso abrangeu a utilização de e-mail e pesquisas em sites. Para avaliação do aprendizado adquirido, foi aplicado um questionário de autoavaliação, em dois períodos (antes e após a conclusão do curso), o qual possibilitou a observação da evolução dos indivíduos participantes no que diz respeito a conhecimento e habilidade nos temas abordados em aula. Realizou-se análise estatística descritiva. A média de desempenho dos participantes foi calculada por ponto e por intervalo de 95% de confiança (IC95%) no momento inicial e final do curso. A comparação entre as médias foi realizada utilizando o Teste t Student pareado. O nível de significância adotado foi de 5%. Observou-se que a aprendizagem em informática nos indivíduos participantes melhorou significativamente após a aplicação do curso avaliado (Teste t Student: -5,360, p<0,001, p2=0,628, =0,999), porém 72,2% dos mesmos relataram não saber anexar um arquivo em uma mensagem a ser enviada por e-mail, bem como, possuir habilidade nula ou baixa para essa atividade. Conclui-se que o curso avaliado promoveu melhora nos conhecimentos e habilidades em informática nos indivíduos participantes.
Avaliação de um curso sobre internet para terceira idade
Keywords: Informatiion; Education; Senior citizens; Informática; Educação; Terceira idade